Banking and the Macroeconomy: A Micro-Macro Linkage - Swetlana Kreiser; Thomas Kick; Christian Merkl; Benedikt Ruprecht (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In this paper, we modify the model by Gertler and Karadi (2011) such that it can be calibrated to the empirical elasticity of bank loan supply with respect to bank capital changes. We estimate this elasticity based on microeconomic data for all German banks. Their business model resembles that of the banks in the model. We find that the estimated elasticity is 0.3, which is substantially lower than the implied elasticity of 1 in the baseline model. Nevertheless, even when calibrating the model to the significantly lower partial equilibrium elasticity, the banking sector remains an important source and amplifier for the macroeconomy. This is due to general equilibrium effects, which play an important role in the transmission of the shocks. We show that the lower elasticity has a dampening effect but the precise quantitative implications depend on the responsiveness of the banks' loan supply to different aggregate shocks.
Keywords: D53; G01; G21; 330